A perspective on oligonucleotide therapy: Approaches to patient customization - Thakur, Shikha; Sinhari, Apurba; Jain, Priti; Jadhav, Hemant R. (Frontiers in Pharmacology, 2022)
The recent surge in approved oligonucleotide therapeutics (OT) indicates the imminent potential of these therapies. Antisense RNAs, MicroRNA, small interfering RNA, and aptamer OT are promising agents for various diseases, including neurodegenerative disorders, cancer, and even orphan diseases. This review highlights oligonucleotide-based drug therapy, landmark discoveries in this field, advantages, disadvantages, and different types of RNA-based therapeutics with their underlying mechanism of action. It also encompasses the challenges and bottlenecks of nucleic acid therapeutics and recent advances made by the scientific community to tackle these, like bioconjugation and chemical modifications. Further, this review deliberates on a newly emerging approach to personalized treatment for patients with rare and fatal diseases with OT.